Dibasic Derivatives of Phenylcarbamic Acid against Mycobacterial Strains: Old Drugs and New Tricks? - Malík, Ivan; Csöllei, Jozef; Solovič, Ivan; Pospíšilová, Šárka; Michnová, Hana; Jampílek, Josef; Čížek, Alois; Kapustíková, Iva; Čurillová, Jana; Pecháčová, Mária; Stolaříková, Jiřina; Pecher, Daniel; et al. (Molecules (Basel, Switzerland), 2018)
In order to provide a more detailed view on the structure⁻antimycobacterial activity relationship (SAR) of phenylcarbamic acid derivatives containing two centers of protonation, 1-[2-[({[2-/3-(alkoxy)phenyl]amino}carbonyl)oxy]-3-(dipropylammonio)propyl]pyrrolidinium oxalates (1a⁻d)/dichlorides (1e⁻h) as well as 1-[2-[({[2-/3-(alkoxy)phenyl]amino}carbonyl)oxy]-3-(di-propylammonio)propyl]azepanium oxalates (1i⁻l)/dichlorides (1m⁻p; alkoxy = butoxy to heptyloxy) were physicochemically characterized by estimation of their surface tension (γ; Traube's stalagmometric method), electronic features (log ε; UV/Vis spectrophotometry) and lipophilic properties (log kw; isocratic RP-HPLC) as well. The experimental log kw dataset was studied together with computational logarithms of partition coefficients (log P) generated by various methods based mainly on atomic or combined atomic and fragmental principles. Similarities and differences between the experimental and in silico lipophilicity descriptors were analyzed by unscaled principal component analysis (PCA). The in vitro activity of compounds 1a⁻p was inspected against Mycobacterium tuberculosis CNCTC My 331/88 (identical with H37Rv and ATCC 2794, respectively), M. tuberculosis H37Ra ATCC 25177, M. kansasii CNCTC My 235/80 (identical with ATCC 12478), the M. kansasii 6509/96 clinical isolate, M. kansasii DSM 44162, M. avium CNCTC My 330/80 (identical with ATCC 25291), M. smegmatis ATCC 700084 and M. marinum CAMP 5644, respectively. In vitro susceptibility of the mycobacteria to reference drugs isoniazid, ethambutol, ofloxacin or ciprofloxacin was tested as well. A very unique aspect of the research was that many compounds from the set 1a⁻p were highly efficient almost against all tested mycobacteria. The most promising derivatives showed MIC values varied from 1.9 μM to 8 μM, which were lower compared to those of used standards, especially if concerning ability to fight M. tuberculosis H37Ra ATCC 25177, M. kansasii DSM 44162 or M. avium CNCTC My 330/80. Current in vitro biological assays and systematic SAR studies based on PCA approach as well as fitting procedures, which were supported by relevant statistical descriptors, proved that the compounds 1a⁻p represented a very promising molecular framework for development of 'non-traditional' but effective antimycobacterial agents.
Keywords: Ethambutol; Oxalates; Isoniazid; ciprofloxacin; Azepines; Computer Simulation; Phenylcarbamates; ethambutol; Ofloxacin; počítačová simulace; dibasic phenylcarbamates; Mycobacterium tuberculosis; lipophilicity; surface tension; Microbial Sensitivity Tests; Ciprofloxacin; Mycobacterium spp.; ofloxacin; pyrrolidiny; Pyrrolidines; Antitubercular Agents; vztahy mezi strukturou a aktivitou; racionální návrh léčiv; isoniazid; Mycobacterium smegmatis; azepiny; oxaláty; fenylkarbamáty; Solubility; Mycobacterium avium; Drug Design; mikrobiální testy citlivosti; Structure-Activity Relationship; rozpustnost; Mycobacterium; Mycobacterium kansasii; electronic properties; antituberkulotika